Gen Z @ work how the next generation is transforming the workplace - Stillman, David; Stillman, Jonah (Harper Business, an imprint of HarperCollinsPublishers, 2017)
A generations expert and author of When Generations Collide and The M-Factor, teams up with his seventeen-year-old son to introduce the next influential demographic group to join the workforce...Generation Z. At 72.8 million strong, Gen Z (born between 1995 and 2012) is about to make its presence known in the workplace in a major way, and employers need to understand the differences that set them apart. They're radically different than the Millennials, and yet no one seems to be talking about them...until now. This generation has an entirely unique perspective on careers and how to succeed in the workforce. Based on the first national studies of Gen Z's workplace attitudes; interviews with hundreds of CEOs, celebrities, and thought leaders on generational issues; cutting-edge case studies; and insights from Gen Zers themselves, Gen Z @ Work offers knowledge today's leaders need to get ahead of the next gaps in the workplace and how best to recruit, retain, motivate, and manage Gen Zers